The Effect of Motivation in Teaching Teenagers - Abdullaeva Lazizakhon (International Journal on Integrated Education, 2022)
The following article is a case study which investigates the effect of motivation in teaching teenagers and its impact on developing their language skills. The work was done manipulating a comparative research method during a teaching period comprising three steps. Observation and data collection revealed that motivation plays a crucial role in learning success and proves that being unstable motivation is required by learners of that age.